Pedicled descending branch latissimus dorsi mini‐flap in repairing partial mastectomy defect: Shoulder functional and esthetic outcomes. Issue 3 (5th June 2019) - Zhou, Lihuan; Wang, Yan; Cai, Ruizhao; Huang, Junhao; Li, Xing; Xie, Zeming; Wang, Jin; Sun, Ya; Chang, Edward I.; Tang, Jun
Abstract: Background: The axillary‐approach pedicled descending branch latissimus dorsi (LD) mini‐flap presents clear benefits in repairing partial mastectomy defects. This study assessed the functional and esthetic outcomes of this flap compared with conventional breast‐conserving surgery (BCS). Methods: From October of 2015 to March of 2017, patients with early breast cancer were enrolled and assigned to the LD group or conventional BCS (CCS) group according to the need of using the pedicled descending branch LD mini‐flap for volume replacement. Muscle strength and range of motion (ROMs) of bilateral shoulders, a disabilities of the arm, shoulder and hand (DASH) questionnaire, and an esthetic evaluation were conducted in all patients at 1 year after surgery. Results: Thirty‐two patients were assigned in the LD group, and 28 in the CCS group. There was no significant difference in muscle strength, ROMs of the shoulder or DASH scores between LD and CCS groups. The results of esthetic survey also revealed a similarly high level of esthetics in both groups. Donor‐site seroma occurred in three patients in the LD group, and no other complication was observed. Conclusions: The pedicled descending branch LD mini‐flap enabled larger excision with favorable esthetics, minimal functional impairment, low rate of complications, and high level of satisfaction.